Contrastive analysis of the segmental phonemes of English and Hausa languages - Md Rashid, Sabariah; Malah, Zubairu (Premier Publishers, 2015)
The objectives of this study are: (1) to identify the similarities and differences between the segmental phonemes of English and Hausa languages, and (2) to predict learning difficulties among the Hausa ESL learners based on this comparison. Learners of English as a second language (L2) are usually faced with difficulties largely contributed by the features of their first languages (L1). The Hausa speakers in Nigeria learn English as a second language and features of the Hausa language are heavily evident in their spoken English. Among the causes of difficulty in pronouncing English among the Hausa speakers is the segmental deviation. This study compares and contrasts the segmental phonemes of English and Hausa. Behaviorists and Structural linguists in the 1950’s and 1960’s founded the theoretical foundations of the Contrastive Analysis (CA) and since then, this approach has been employed in the second language acquisition studies. In the course of this study, the researchers employed desk research where data were drawn from archive and then analyzed side-by-side revealing their similarities and differences. The results of the study demonstrate that although Hausa and English have some similar phonemes, the sounds do not behave the same way in the two languages, and Hausa has 47 phonemes when English has 44. Differences in the phonological features between the two languages result in challenges faced by the Hausas in learning English.